The evolution of aquatic craftsmanship in historical societies and its impact on modern knife making and pottery - Normirzaev, Abdukayum; Ergashev, Rustam; Akhmedov, Jasurbek; Toshov, Kamoliddin; Yuldasheva, Dilnoza; Saparbaeva, Erkinoy; Usmonov, Murtoz; Madraimov, Askariy (International Journal of Aquatic Research and Environmental Studies, 2025)
The development of aquatic craftsmanship demonstrates the impact of water communities, with state-of-the-art artisanal technologies growing around water bodies. This examines the influence of innovative actions on ancient knifemaking and pottery craftsmanship practices on the development of early river and later maritime cultures. Civilizations growing along the Nile, the Indus, and the Aegean coasts, and later inland as far as the Marshlands of southern Iraq, worked with water and incorporated it as transformative in the industrial production of worked materials. Water was critical for metal tempering, clay refining, and design aesthetics shaped in patterned fluidity and natural forms. This drew on archaeological sites and ethnographic accounts, as marshlands and water worked strongly with the selection of materials and tools for the functional and symbolic crafts. This paper additionally examines the ways in which current artisans engage with such historical practices using approaches that are ecologically conscious as well as technologically advanced and refined. Today's knifemakers and potters are still employing ancient water-based techniques such as water quenching, slip casting, and hydrodynamic shaping to attain the precision, durability, and beauty of their products. This study expresses an ecological and cultural legacy of water based craftsmanship and advocates for the preservation of water-oriented artisan knowledge systems integrated with new approaches that contemporary principles of ecological balance and symmetry in design propose.
Keywords: Aquatic craftsmanship, Knifemaking, Pottery, Waterborne cultures, Material evolution, Maritime archaeology, Eco-craft design